Analisis Perilaku Konsumtif Remaja terhadap Penggunaan Shopeepay Ditinjau dari Etika Konsumsi dalam Islam Studi Kasus pada Desa Pagerbarang - Dwi Amanatun Nisa; Nurul Wulandari Putri (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
This study aims to examine the consumer behavior of teenagers in pagerbarang village in using ShopeePay and analyze it from the perspective of Islamic consumption ethics. Data were collected through in-depth interviews with twenty teenagers selected using the snowball sampling technique. The results indicate that consumer behavior is influenced by discounts, promotions, transaction convenience, and social pressure. Teenagers tend to make impulsive purchases driven by emotional needs and low financial literacy. From the perspective of Islamic consumption ethics, such behavior contradicts the principles of moderation (qanâ’ah) and prohibition of extravagance (israf). Teenagers often overlook these values due to social and technological influences that facilitate easy transactions. Therefore, increasing awareness of financial literacy and religious values is crucial to fostering more prudent consumer behavior.